Comparison of Stutterers and Normals on Sacks Sentence Completion Test in Kannada SSCT (K) - Devaki R (Journal of All India Institute of Speech and Hearing, 1970)
Interest in the personality of stutterers is as old as the history  of the dis- order itself.  Bender (1942) found a greater tendency toward introversion, neuro- ticism, of being less dominant, less sociable and having less self-confidence, when compared with a matched control group.